2007
DOI: 10.1007/s10552-006-0111-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological attitudes and risk of breast cancer in Japan: a prospective study

Abstract: Although further studies will be necessary to verify these findings, our results suggest that having "ikigai" and being decisive decrease an individual's subsequent risk of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
0
19
2
1
Order By: Relevance
“…However, recent meta-analyses have shown that depression and stress-related psychosocial factors are associated with an increased risk of site-specific cancer incidence [34,35]. Previous analysis on association of ikigai with breast cancer incidence by using data obtained in the JACC study has also shown that women with ikigai had a significantly lower risk of breast cancer incidence [29]. Psychological factors might be associated with incidence of cancer in a certain site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent meta-analyses have shown that depression and stress-related psychosocial factors are associated with an increased risk of site-specific cancer incidence [34,35]. Previous analysis on association of ikigai with breast cancer incidence by using data obtained in the JACC study has also shown that women with ikigai had a significantly lower risk of breast cancer incidence [29]. Psychological factors might be associated with incidence of cancer in a certain site.…”
Section: Discussionmentioning
confidence: 99%
“…Four possible answers were provided: 'definitely yes,' 'yes,' 'not particular,' and 'no' [29]. For the analysis, these responses were categorized into two groups as follows: subjects who answered 'definitely yes' or 'yes' were defined as those with ikigai, and subjects who answered 'not particular' or ' no' were defined as those without ikigai.…”
Section: Evaluation Of Ikigaimentioning
confidence: 99%
“…A Japanese study reported that the lack of ikigai was significantly associated with CVD mortality, but not cancer mortality (11). On the other hand, another study reported that the lack of ikigai was associated with an increased risk of breast cancer (17).…”
Section: Introductionmentioning
confidence: 98%
“…T he psychological factors of people play important roles in the morbidity and mortality risks (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Studies in the US and Europe have reported that the negative psychological factors, as represented by factors such as a low subjective sense of well-being (1), dissatisfaction (2)(3)(4), hopelessness (5,6), and self-perception of ill health (7)(8)(9), were associated with an increased risk of all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies document links between wellbeing or positive affect and favorable health outcomes (Boehm et al, 2011; Chida & Steptoe, 2008; Feller et al, 2013; Martín-María et al, 2017; Wakai et al, 2007). What is, however, unclear, is the extent to which these associations are largely consistent across cultures versus varying across cultures that differ in cultural dimensions related to social networks.…”
Section: Introductionmentioning
confidence: 99%